Short pulse of 1080 improves the survival of brown kiwi chicks in an area subjected to long-term stoat trapping. Issue 4 (1st October 2016) - Robertson, HA; Craig, E; Gardiner, C; Graham, PJ
ABSTRACT: Many mainland populations of kiwi are declining because stoats ( Mustela erminea ) kill most of their chicks. Stoats are often trapped during conservation programmes, but the long-term effectiveness of trapping has not been measured. During continuous trapping of mammalian predators in the 9800 ha Whangarei Kiwi Sanctuary, the survival of brown kiwi ( Apteryx mantelli ) chicks declined over time. Following the use of sodium fluoroacetate (1080) to kill rats ( Rattus spp.) and possums ( Trichosurus vulpecula ) and likely secondary poisoning of stoats, chick survival at Riponui increased from 5% to 56%, and the 62% chick survival at Rarewarewa was better than the 20% recorded in a trapped-only area nearby. We suggest that untrappable stoats accumulate in areas subjected to continuous predator trapping. Conservation managers should build into their long-term pest control programmes a periodic pulse of an alternative tool to kill pests that, for whatever reason, actively avoid the primary control tool.